KOMUNIKASI MANAJEMEN ALA GURU YESUS - Gunadi, YS (Universitas Prof. Dr. Moestopo (Beragama), 2006)
Preparations of Communicating Management, Studies about planning the publicity program: news and publicity; planning publicity; arranging for approvals; organizing the files; controlling rumors, special events, product publicity; media of publicity; broadcast and composite reports, etc.Basic of the title âKomunikasi Manajemen Ala Guru Yesus/Management Communications Ala Teacher Yesus â, for a long along ago. He Gave order to the Twelve disciples and sent them out to preach the kingdom of god and to heal the sick. Their make some planning.Â Publicity program, special event, etc, where be actions at sinagoges, markets, crowds, villages, gardens, towns, near lake, outbound and so on. The disciples left and traveled through all villages, preaching communication the God news to people in everywhere with secial method of LOVEâ